A fatal case of DRESS induced by strontium ranelate associated with HHV-7 reactivation. Issue 3 (March 2016) - Drago, F.; Cogorno, L.; Broccolo, F.; Ciccarese, G.; Parodi, A.
Abstract We report the first case of drug rash with eosinophilia and systemic symptoms (DRESS) following strontium ranelate (SR) treatment associated with systemic human HHV-7 reactivation. DRESS syndrome is a severe adverse drug-induced reaction presenting as a diffuse maculopapular skin rash with fever, hematological abnormalities (leukocytosis, eosinophilia, and/or atypical lymphocytosis), and multiorgan involvement. In our patient, diagnosis of DRESS was confirmed by the presence of six of the seven diagnostic criteria established in 2006 by the Japanese Research Committee on Severe Cutaneous Adverse Drug Reaction: maculopapular skin rash developing at least 3 weeks after starting therapy with a limited number of drugs, prolonged clinical symptoms after discontinuation of the causative drug, lymphadenopathy, fever, leukocyte abnormalities, and liver abnormalities. The diagnostic criteria of human herpesvirus (HHV)-6 reactivation have not been fulfilled in our patient, but a HHV-7 active infection was demonstrated by the presence of HHV-7 DNA and IgM in the patient's serum. In fact, in some DRESS instances, reactivation of HHVs other than HHV-6 may be detected, including HHV-7, Epstein-Barr virus (EBV), and cytomegalovirus (CMV). Our case underlines that not only HHV-6 but also HHV-7 systemic reactivation may be associated with a more severe and even fatal course of this syndrome.